Local preferences for three indigenous oil-seed plants and attitudes towards their conservation in the Kénédougou province of Burkina Faso, West-Africa - Tiétiambou, Fanta Reine Sheirita; SALAKO, Kolawolé Valère; Tohoun, Jésukpégo Roméo; OUÉDRAOGO, Amadé (My University, 2020)
Carapa procera, Lophira lanceolata, and Pentadesma butyracea are three underutilized but increasingly threatened indigenous oil-seed tree species (IOS) in tropical Africa. Because local knowledge is vital for sustainable management, this study investigated the socio-economic factors that explain local people’s (i) preferences for these IOS, (ii) attitudes toward their conservation, and (iii) ability to identify “plus trees” based on seed traits. We predicted a positive relationship between response variables and informants’ age, residence status, gender (femaleness), and existence of market opportunities for each IOS. We also predicted that a higher preference for a given IOS has a positive effect on people’s attitudes for its conservation and the aptitude to identify its “plus trees.” We additionally expected significant differences among ethnic groups for each response variable. Data were collected through individual semi-structured interviews with 336 informants from 14 randomly selected villages in the species distribution area of Kénédougou province. For each species, the collected data were the number of actual uses reported (converted to use value—UV, as a measure of the species preference), practiced conservation actions (converted to conservation attitude using a four-scale scoring method), and possible criteria for selecting preferred trees for seed oil extraction. Generalized linear mixed models were used to test for the fixed effects of socio-economic factors, and account for the random variation across villages. The results showed species-specific patterns. Carapa procera had the highest UV and hence was the most preferred IOS, particularly by women. Informants from the Siamou ethnic group had the highest UV irrespective of IOS. The most cited conservation actions were assisted natural regeneration and banning of tree cutting, which were practiced for C. procera and L. lanceolata. No conservation measure was cited for P. butyracea. The practice of tree planting was not recorded for any of the IOS. Young and male informants participated less in conservation actions. Tree selection for oil-seed collection was mainly guided not by “oil extraction yield” but rather by the “quality of extracted oil” (namely oil color and taste for food uses, and oil bitterness for medicinal efficacy). The selection mainly concerned L. lanceolata and was mostly practiced by elderly people. This study provided useful local knowledge-based information to guide conservation actions and valorization strategies of three IOS. The study sheds further light on the socio-economic factors that are associated to local people’s preferences, conservation attitudes, and individual tree selection.
Keywords: • Conservation actions; Local knowledge; Kénédougou; Plus-tree; Underutilized-plants; Use value